2019
DOI: 10.1186/s12885-019-5286-0
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus and breast cancer: the role of inflammation and viral expressed proteins

Abstract: BackgroundBreast cancer is currently the most common neoplasm diagnosed in women globally. There is a growing body of evidence to suggest that human papillomavirus (HPV) infection may play a key role in invasiveness of breast cancer. The aim of this study was to determine the presence of HPV in patients with breast cancer and its possible association with cancer progression.MethodsBreast specimens were collected from 72 patients with breast cancer and 31 healthy controls. The presence of HPV was investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 62 publications
(83 reference statements)
10
77
0
6
Order By: Relevance
“…Human papillomavirus (HPV) belongs to the family of Papillomaviridae having various hosts in both humans and animals. 105,106 More than 200 types of HPV have been identified, and HPV infections are generally classified as high-risk or low-risk HPV. Twenty high-risk types (e.g., 18,26,31,33,39,45,etc.…”
Section: Mir-146a In Papillomavirusesmentioning
confidence: 99%
“…Human papillomavirus (HPV) belongs to the family of Papillomaviridae having various hosts in both humans and animals. 105,106 More than 200 types of HPV have been identified, and HPV infections are generally classified as high-risk or low-risk HPV. Twenty high-risk types (e.g., 18,26,31,33,39,45,etc.…”
Section: Mir-146a In Papillomavirusesmentioning
confidence: 99%
“…After the elimination of the triggering stimulus and the resolution of the injury, inflammation should be disabled in a programmed manner. However, if the stimulus is persistent, the acute inflammation becomes chronic in nature, and evidence suggests that chronic inflammation is strongly associated with cancer . About 20% of human cancers are associated with chronic inflammation caused by infectious agents, autoimmune diseases and long‐term exposure to irritants and other noxious agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the stimulus is persistent, the acute inflammation becomes chronic in nature, and evidence suggests that chronic inflammation is strongly associated with cancer. 10,13,14 About 20% of human cancers are associated with chronic inflammation caused by infectious agents, autoimmune diseases and long-term exposure to irritants and other noxious agents. Common causes of persistent inflammation that lead to cancer development, include infection with hepatitis C or B viruses that lead to hepatocellular carcinoma, inflammatory bowel disease that leads to colorectal cancer and infection with Helicobacter pylori that leads to gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been hypothesized that hormone dependent oncogenic viruses, such as HPV may have causal roles in some cancers [38]. Expression of and high risk HPV DNA in BC [39] and HPV proteins in cervical cancer [40] was recently reported. In this study, we demonstrated the presence of high-risk HPV in the tissues of 20% of breast cancer specimens.…”
Section: Cd8+ T Lymphocytes and Cd4+ T Helper Cells May Promote Tumormentioning
confidence: 99%